Aesthetics and beautiful lifestyle - Redefining the concept of aesthetics in the built environment - Mohd Nawawi, Norwina (2009)
The question of aesthetic is an age long enigma in many societies with various conceptions and perceptions through philosophers of yore till the present day. Beauty, as part of aesthetics, carries along its intonation in more that just physical expressions but to experiencing life itself in the manner manifested by the Creator for mankind surpassing time. For built environment, the enigma of aesthetics can be expressed in many ways to include the integration of nature with man’s handiwork to the land itself in intrigue balance; the shaping of human’s life with the planning of friendly neighbourhood and efficient cities for sustainability; and the fiddling of spatial concerns with a purpose to ease Man’s pursuit to submission to the Almighty. We are created in many shades, shapes, colour, culture and other diversities to provide constant enrichment to life’s innovation in positive way. The perception of aesthetics into beautiful lifestyle conjures images of pure joy and exuberance in many aspects of mankind and the environment. The notion of beautiful living must be based on matter that provide joyfulness and sense of fulfilment here and the hereafter and not on trends and fleeting moments of desire. The presentation thus is not conclusive in determining the concept of aesthetic and beautiful lifestyle but merely to address the questions and opens more enquiry of its deliverance in architecture, landscape architecture, planning and other aspects of the built environment. Keywords: aesthetics, beautiful, lifestyle, perception, built environment